Numerical simulation of the flow passing through the side weir-gate - Kartal, Veysi; Emiroglu, M. Emin (Elsevier Sci Ltd, 2024)
A combination of a weir and a gate is called the combined weir-gate. The hydraulic behaviour of the combined side weir-gate was numerically and experimentally investigated in the study. The findings were evaluated to investigate the impact of combined flow and weir-gate geometry characteristics on the discharge capacity of the side weir-gate. Thirty-three numerical simulations were conducted. The numerical simulations were performed by applying the Volume of Fluid (VOF) method to the Reynolds-averaged Navier-Stokes (RANS) equations using Flow-3D using k-epsilon turbulence model. The model was validated against experimental data previously obtained by the authors, and eighty-eight experiments were conducted to analyze using different models. The findings show that the models with rectangular weir and gate cross-sections have higher discharge capacity than those with triangular and semicircular gates, and the models with semicircular gates have higher discharge capacity than those with triangular gates. The Absolute Percentage Error (APE), Root Mean Square Error (RMSE), Scatter Index (SI) and Coefficient of Determination (R2) of the numerical and experimental results are 4.11 %, 0.30 % and 0.10 %, 0.99, respectively. The results show that experimental and numerical findings and discharge capacity are consistent.
Keywords: Side weir-gate; Discharge capacity; Numerical simulation; Flow-3D